2020
DOI: 10.3390/s20082294
|View full text |Cite
|
Sign up to set email alerts
|

IoT-RECSM—Resource-Constrained Smart Service Migration Framework for IoT Edge Computing Environment

Abstract: The edge-based computing paradigm (ECP) becomes one of the most innovative modes of processing distributed Interneit of Things (IoT) sensor data. However, the edge nodes in ECP are usually resource-constrained. When more services are executed on an edge node, the resources required by these services may exceed the edge node’s, so as to fail to maintain the normal running of the edge node. In order to solve this problem, this paper proposes a resource-constrained smart service migration framework for edge compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We use node 5 as an example for evaluation. We point out that any fog node produces the same result for the given input configuration, because we assume that all individual external arrival rates are set to be identical, which means that the individual effective arrival rates λ i , 1 ≤ i ≤ n, will be the same according to Equation (6). The above assumption and the obtained identical effective arrival rates λ i will cause the visit ratio v 5 not to change with different values of the total external arrival rate γ.…”
Section: Numerical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…We use node 5 as an example for evaluation. We point out that any fog node produces the same result for the given input configuration, because we assume that all individual external arrival rates are set to be identical, which means that the individual effective arrival rates λ i , 1 ≤ i ≤ n, will be the same according to Equation (6). The above assumption and the obtained identical effective arrival rates λ i will cause the visit ratio v 5 not to change with different values of the total external arrival rate γ.…”
Section: Numerical Evaluationmentioning
confidence: 99%
“…Fog computing is especially important in IoT deployment as it frees resource-constrained IoT devices from having to frequently access the resource-rich cloud [6]. Since the IoT tasks of requesting fog computing resources and service types are variable, dynamically provisioning fog computing resources to ensure optimum resource utilization and at the same time meet a certain constraint will not be an easy task.…”
Section: Introductionmentioning
confidence: 99%
“…In [29], Edge Computing has been incorporated to help heterogeneous IoT systems communicate through specific network topology, different devices (sensors, cars, machines, computers, metering computers, etc.). In [30], the authors suggest that several disciplines will benefit from IoT smart grid solutions such as Business 4.0, Energy Management and Prosumers, and will support many academics and industries. The heterogeneous data collected and generated by IoT devices can be used to provide advanced computing technology solutions for infrastructure according to the three-tier computing infrastructure (IoT-Sensors, Cloud-Services and Edge Nodes) [31].…”
Section: Introductionmentioning
confidence: 99%
“…This will connect cloud storage, networks and databases. In [ 28 , 29 ], the authors suggested that edge computing would enhance reaction times, reduce energy rates and increase interactions, scalability and confidentiality. Edge computing helps heterogeneous IoT systems communicate through unique network topology and different devices (sensors, cars, machines, computers, gauges, etc.).…”
Section: Introductionmentioning
confidence: 99%